Thermal diffusivity of zinc-aluminum layered double hydroxide using PVDF photoflash technique - Mat Yunus, Wan Mahmood; Ghaziean, Maryam Ranjbar; Hussein, Mohd Zobir; Lim, Mei Yee (David Publishing, 2010)
Thermal diffusivity of zinc-aluminum layered double hydroxides synthesized at different molar ratios of Zn to Al, at pH 7 and 8 were measured using polyvinlidene diflouride (PVDF) photoflash technique. The samples were prepared using Zn(NO3)2 and Al(NO3)2 solutions by dropwise addition of NaOH solution with vigorous stirring under nitrogen atmosphere. The different ratios of Zn to Al were obtained by changing the molar ratio of Zn(NO3)2 to Al(NO3)2 solutions. The slurry formed was kept at 70 ˚C in an oil bath shaker for 18 h and then filtered, washed and dried in an oven for another 48 h at 70 ˚C. A simple photoflash and PVDF transducer were used as light source and thermal wave detector, respectively. All the measurements of thermal diffusivity of Zn-Al layered double hydroxide were carried out at room temperature. For Zn/Al > 3, the thermal diffusivity of all series of sample prepared at pH = 7 and 8 increase with the increasing of Zn composition. Thermal diffusivity values of zinc-aluminum layered doubled hydroxide synthesized at pH 8 are higher than the values obtained for samples prepared at pH = 7 except for Zn/Al higher than 5.